Atividade antioxidante e citotóxica do extrato e frações das folhas de Syzygium malaccense em células de melanoma cutâneo - Silva, Cleidiane da (2021)
Syzygium malaccense is a plant of the Myrtaceae family of Asian origin. The fruit and ornamental tree has adapted to the hot climate regions of Brazil, being known in the country as Jambo. It is widely used in traditional medicine because of its potential anti inflammatory and hypoglycemic action. Promising results were presented in some studies with the leaves of S. malaccense, however, there is still little information about its chemical composition and biological activities, mainly about the species found in Brazil. In this sense, this study evaluated the antioxidant and cytotoxic capacity of substances present in the leaves of S. malaccense, with tests of antioxidant activity attributed to the scavenging capacity of DPPH and ABTS radicals, iron reduction (FRAP) and reduction of the Folin Ciocalteu reagent (FCR). Cytotoxicity was evaluated by cell migration and cell viability (MTT) assays in cutaneous melanoma cancer cells (SK MEL 28) treated with crude extract, acetone fraction and three subfractions of the plant, the acetone fraction being chosen because it presents good yield and high potential against antioxidant assays. The oxidative and inflammatory markers were also evaluated from the analysis of substances reactive to thiobarbituric acid (TBARS), nitric oxide (NO), myeloperoxidase (MPO) and the determination of the content of ascorbic acid (vitamin C). The results demonstrate that the purification of the hydroethanolic extract from the leaves of S. malaccense potentiated the plant's bioactivity and increased the content of the extract's major compounds in the subfractions, which showed relevant cytotoxic activity in cutaneous melanoma cells, as well as high antioxidant and a composition rich in flavonoids. Two compounds with high purity were isolated from the most bioactive subfractions by preparative CCD, one of them being identified by HPLC DAD as the glycosylated flavonoid myricitrin and the other compound, not yet identified, referring to the more intense signal of the subfractions. Thus, this study presents important information about the bioactivity of the compounds present in the leaves of S. malaccense collected in the Southeast region of Brazil, bringing unprecedented results regarding the in vitro toxicity of the plant in cutaneous melanoma cells.